Malleable Penile Implant Rod Diameter Predicts Complications and Patient Satisfaction. Issue 2 (23rd February 2022) - Habous, Mohamad; Omar, Mohamed; Farag, Mohammed; Abdelwahab, Osama; Laban, Osama; Binsaleh, Saleh; Mulhall, John P.; Ralph, David; Aziz, Mohammed
Abstract: Background: One of the most common complaints after malleable prosthesis implantation (MPI) is thinning of the penis and decreasing girth. Some surgeons try to insert the largest diameter they can to improve patient satisfaction Aim: To investigate if malleable rod diameter (MRD) has an impact on outcome and patient satisfaction Methods: Consecutive malleable prosthesis implantation (MPI) was assessed in a high-volume center over 1 year. The same preoperative, intraoperative, and postoperative protocols were used for all patients and one brand of the malleable device was used only. We recorded MRD and length for all patients. All patients had data on comorbidities including glycated hemoglobin (HbA1c) and clinical Peyronie's disease (PD). Revision cases and those who lost for follow-up were excluded from the study. We also excluded patients operated on by low-volume surgeons. All complications, minor (edema, ecchymosis, pain), and major (infection and erosion) were recorded. After 1-year, patients were assessed and given a Likert scale from 1 to 5 where 5 is most satisfied with their MPI. We stratified patients according to MRD into 2 groups: group A for diameter 9.5 and 11 mm and group B for 13 mm. Outcome: : Larger diameter of malleable penile implants may be associated with more complications Results: 183 patients had full data and filled the questionnaire after 1-year follow-up. All patients had Coloplast, Genesis penile implants. Major complications rate (infection, erosion, and removal) was significantly higher in group B 11% vs 1.2% in group A ( P  = .016). At 4 weeks postoperative visit, 90 % of group A showed no complications vs 60% only in group B that was statistically significant ( P  = .0003). Satisfaction rate was more in patients in group A (88.6%) compared to patients in group B (75.7%) but this did not reach to be statistically significant ( P  = .0519) Clinical Implications: MRD predicts outcome. Strengths & Limitations: The strengths of our study include that it is the first prospective study with good number of malleable implants. Limitations include: no validated satisfaction instrument and MRD choice was based on surgeon preference. Conclusions: Larger diameter of malleable penile implants are not associated with a higher rate of patient satisfaction